Laboratory growth capacity of an invasive cyanobacterium (Microcystis aeruginosa) on organic substrates from surface waters of permafrost peatlands - Payandi-Rolland, Dahédrey; Shirokova, Liudmila S.; Larieux, Julien; Bénézeth, Pascale; Pokrovsky, Oleg S. (Environmental sciences: Processes and impacts)
Within a global warming trend, invasive cyanobacteria, abundant in tropical and temperate regions, can migrate northward and colonize thermokarst lakes in permafrost-affected territories. For a better understanding of the cyanobacterial proliferation mechanism in those lakes, we performed laboratory growth of typical invasive cyanobacteria, Microcystis aeruginosa, onto various organic-rich solutions representative of permafrost peatlands. Aqueous leachates of lichen, moss and peat were the most favorable substrates for massive growth. The growth in the presence of all organic substrates produced an increase in solution pH by two units and a sizable (30–50%) decrease in the concentration of dissolved organic carbon. The observed increase in the dissolved organic carbon aromaticity degree likely reflected preferential cyanobacterial uptake of aliphatic, optically transparent organic substances. Cyanobacterial growth over a bloom period can create a carbon sink (uptake of 2.5 and 8.3 g C–CO2 m−2 d−1) that can offset the net heterotrophic status of thermokarst lakes in permafrost peatlands, thus switching the lake status from a C source to a C sink. Therefore, predictions of future carbon exchanges with the atmosphere in surface waters of permafrost peatlands require explicit accounting for the possibility of invasive cyanobacterial growth.